Karakteristik mutu sirup bunga telang dengan penambahan beberapa konsentrasi gula cair fruktosa - Prastianingsih, Vida; Yusmarini; Nopiani, Yanti (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2025)
Syrup is a thick beverage product that has a high sucrose content. The fructose liquid sugar can be used as a sweetener butterfly pea flower syrup. The purpose of this research is to get the right concentration of fructose liquid sugar and good quality and fulfill SNI 3544: 2013 about syrup. This research was conducted experimentally by using a completely randomized design with four treatments and four replications. The treatment in this study is the concentration of fructose liquid sugar (45%, 50%, 55% and 60%). The data obtained were statistically analyzed using analysis of variance and continued with Duncan's Multiple Range Test (DMRT) at the 5% level. The result of this research showed that the concentration of fructose liquid sugar significantly affected sensory characteristics of viscosity before adding water. The best treatment in this research was S3 treatment (55% fructose liquid sugar) where pH 4.55, reducing sugar content 11.4%, viscosity 853.4 cP, total plate count 0.99 CFU/mL, and antioxidant activity IC50Â 25.42 ppm. The descriptive assessment is that theÂ color is purplish blue, scented with sugar and butterfly pea flower, moderately sweet taste and slightly thick. Butterfly pea flower syrup in all treatments has met the quality requirements of SNI 3544: 2013 syrup.